The advantages and disadvantages of the farmer - Harner, J. N. (My University, 1892)
Introduction: The politician in every speech he makes tells us that the farmer is the hub of the wheel of progress, and appeals, to him, as the originator of wealth, and, as one of a sound and practical, turn of mind for his support in the coming election. The Fourth of July, orator spares no pains and no rhetorical figures in speaking of the great rural classes. For all of this enthusiastic oratory the farmer has his joys, and his sorrows, his fortunes, and his misfortunes, his advantages and his disadvantages. When living several miles from the noisy and busy city, or perhaps even a mile or more of forest, field, or prairie is stretched between him and his nearest neighbor, the farmer can realize as no one else the enjoyment to be found in an hours conversation. The few spare evenings that he may chance to have must be spent in the same old way – the same old routine is to be repeated. There are no good social entertainments within a block of his door, and the lecture room is but rarely seen. The soul, thrilling and inspiring religious services that are so characteristic of the city cannot be participated in and the cold wintry days cannot always be spent in the most profitable manner. There he lives in partial seclusion from society, and must devise his own method of entertainment.
Citation: Harner, J. N. The advantages and disadvantages of the farmer. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Agriculture; Society; Advantages; Disadvantages; Farmer; Theses; Manuscripts (documents)